A school-leaving examination in English for Thai lower secondary school students - Wilai Panpanich 1941- ([Quezon City publisher not identified], 1969)
The purpose of the study is to prepare an objective test of two forms based on second language teaching and testing principles designed to measure achievement in English of Thai third year high school students. The study is an attempt to improve the technique and content of English examinations.
Thesis (Master in Education)--University of the Philippines.
Typescript
Keywords: English language -- Examination